PENGUATAN LITERASI AKADEMIK MELALUI PELATIHAN KARYA TULIS ILMIAH UNTUK MEMBANGUN GENERASI CENDIKIA DI MAN INSAN CENDIKIA BANGKA TENGAH - Kusmita, Tri; Puspita, Indah; Indriawati, Anisa; Saputri, Riny (Fakultas Sains dan Teknik, Universitas Bangka Belitung, 2024)
The training on scientific writing (KTI) for teachers at MAN Insan Cendikia Bangka Tengah represents a strategic step to enhance scientific literacy, given that KTI is a requirement for graduation and class advancement. This training aims to improve teachers' understanding of scientific writing through a guided tutorial method that combines theory with practical application. This method is designed to assist teachers in grasping the stages of KTI writing, from topic selection to proper citation techniques. Results following the training indicate a significant improvement in teachers' comprehension of KTI writing. Therefore, this training not only strengthens the academic literacy skills of teachers but also prepares them to guide students more effectively, thereby creating a quality educational environment that supports the development of an intellectual generation.